Testing the quality of film-based creative and innovative character education test with rasch model - Gendon Barus; Juster Donal Sinaga; Yustinus Dasilva Moron (Jurnal Konseling dan Pendidikan)
This study aims to test the quality of Film-Based Creative and Innovative Character Education Test by examining the values of validity, reliability, different power, and level of difficulty. This study focuses on the Film-Based Creative and Innovative Character Education Outcomes Test using the 40 items Rasch Model. This research is a research development. Research subjects numbered 66 students in grade VII and VII of junior high school. Data analysis techniques to see the quality of test kits developed in this study using the Rasch Model with QUEST and Ministeps programs. The results showed: (1) the validity of the whole test items fit in the range of INFIT MNSQ 0.80-1.0; (2) the reliability of the test questions is very high with a value of 0.92; (3) the level of difficulty of the midterm test items (-1 to 1) according to the Rasch Model category (-2 to +2); and (4) the power of different test questions is in the good category. The conclusion of this research is that Film-Based Creative and Innovative Character Education Test Results can be used to measure the results of creative and innovative character education in schools.